Exploration on the Influencing Factors of Overseas Students' Online Chinese Learning Intention During the Epidemic Period - Zou, Xiaoyu (Frontiers in Psychology, 2022)
In the information age, online teaching has become an essential field of educational development. The present work aims to study Willingness To Learn (WTL) of Overseas Students (OSs) during the Corona Virus 2019 (COVID-19) pandemic. Consequently, the present work models the influencing factors of OSs' WTL (OSLW) for Online Chinese Learning (OCL) based on the Unified Theory of Acceptance and Use of Technology (UTAUT). Specifically, it takes OSs from five universities in Fuzhou as research subjects. It employs the Questionnaire Survey (QS) to collect data, SPSS25.0 to analyze the reliability and validity of the collected data, and AMOS23.0 to verify the model. The results show that autonomy and self-discipline have become essential factors affecting OSs' OCL, and personal interests and hobbies are the main factors affecting OSs' OCL. Meanwhile, Perceived Interest (PI), Self-Learning Management (SLM), effort expectation, community impact, performance expectation, and facilitating conditions significantly and positively impact OSLW for OCL. Their impact degree ranges from small to large in turn. The research content provides novel Online Teaching and Learning (OTL) strategies for OSs under the COVID-19 pandemic.